Inhaled Technosphere Insulin Versus Inhaled Technosphere Placebo in Insulin-Naïve Subjects With Type 2 Diabetes Inadequately Controlled on Oral Antidiabetes Agents - Rosenstock, Julio; Franco, Denise; Korpachev, Vadym; Shumel, Brad; Ma, Yuhui; Baughman, Robert; Amin, Nikhil; McGill, Janet B. (Diabetes care, 2015)
To investigate the efficacy and safety of prandial Technosphere inhaled insulin (TI), an inhaled insulin with a distinct time action profile, in insulin-naïve type 2 diabetes (T2D) inadequately controlled on oral antidiabetes agents (OADs). Subjects with T2D with HbA1c levels ≥7.5% (58.5 mmol/mol) and ≤10.0% (86.0 mmol/mol) on metformin alone or two or more OADs were randomized to add-on prandial TI (n = 177) or prandial Technosphere inhaled placebo (TP) (n = 176) to their OAD regimen in this double-blind, placebo-controlled trial. Primary end point was change in HbA1c at 24 weeks. TI significantly reduced HbA1c by -0.8% (-9.0 mmol/mol) from a baseline of 8.3% (66.8 mmol/mol) compared with TP -0.4% (-4.6 mmol/mol) (treatment difference -0.4% [95% CI -0.57, -0.23]; P < 0.0001). More TI-treated subjects achieved an HbA1c ≤7.0% (53.0 mmol/mol) (38% vs. 19%; P = 0.0005). Mean fasting plasma glucose was similarly reduced in both groups. Postprandial hyperglycemia, based on 7-point glucose profiles, was effectively controlled by TI. Mean weight change was 0.5 kg for TI and -1.1 kg for the TP group (P < 0.0001). Mild, transient dry cough was the most common adverse event, occurring similarly in both groups (TI, 23.7%; TP, 19.9%) and led to discontinuation in only 1.1% of TI-treated and 3.4% of TP-treated subjects. There was a small decline in forced expiratory volume in 1 s in both groups, with a slightly larger decline in the group receiving TI (TI, -0.13 L; TP, -0.04 L). The difference resolved after treatment discontinuation. Prandial TI added to one or more OADs in inadequately controlled T2D is an effective treatment option. Mild, transient dry cough was the most common adverse event.